AZERBAIJAN NEEDS TO DEVELOP DIGITAL SKILLS FOR A DIGITAL FUTURE (PHILOSOPHICAL ANALYSIS) - Тахмина, Агакишиева (SWorldJournal, 2023)
The article discusses the concept of “digital generation” and gives the history of the emergence of this concept. The author attempts to meaningfully consider the features of the representatives of the “digital generation”. The innovative educational env